Creating Work and Family Balance: Workshop Evaluation - David C. Diehl; Suzanna Smith; Betsy Crisp; Karen S. Headlee (EDIS)
Workshop presenters: the evaluation instrument described in this article provides a simple and streamlined way to conduct a useful evaluation and solicit feedback for program refinement. It was designed to accompany a Florida Cooperative Extension Service workshop, Creating Work and Family Balance. This publication provides support for professionals who are delivering this workshop or workshops with similar objectives. The purposes of the evaluation are to generate information that can be used for program improvement and for reporting impacts in the annual reporting system of Cooperative Extension. This 5-page fact sheet was written by David C. Diehl, Suzanna Smith, Betsy Crisp, Karen S. Headlee, and published by the UF Department of Family Youth and Community Sciences, December 2011.